Long-term trends in the burden of non-rheumatic calcific aortic valve disease in China from 1990 to 2021, with projections to 2050: results from the global burden of disease study - Jian, Bin; Li, Zhen; Huang, Yu; Wei, Zhixiong; Zhao, Gaoyang; Fang, Jun (Frontiers in Medicine, 2025)
BackgroundNon-rheumatic calcific aortic valve disease (NRCAVD) has emerged as a significant health challenge globally, with China’s rapidly aging population bearing a disproportionate burden, necessitating comprehensive epidemiological analysis to guide public health strategies.MethodsUtilizing data from the Global Burden of Disease (GBD) database 2021, we examined the incidence, prevalence, mortality, and disability-adjusted life years (DALYs), along with their corresponding age-standardized rates (ASRs), of NRCAVD in China from 1990 to 2021 and compared these data with global trends. The analysis employed joinpoint regression to calculate the estimated annual percentage change (EAPC) and average annual percentage change (AAPC) for evaluating NRCAVD trends over the past 32 years. Additionally, we employed the Bayesian age–period–cohort model to project these trends through 2050.ResultsThe age-standardized incidence and prevalence rates of NRCAVD in China increased from 1.42 to 2.52 per 100,000 and 17.24 to 32.68 per 100,000, respectively, between 1990 and 2021. Favorably, the age-standardized mortality and disability-adjusted life year rates of NRCAVD decreased from 0.10 to 0.07 per 100,000 and 2.42 to 1.92 per 100,000, respectively. The rates were higher in male individuals than in female individuals across all four metrics over the study period. In China, the estimated annual percentage changes for incidence, prevalence, mortality, and disability-adjusted life years were 2.04, 2.33, −1.34%, and −1.06%, respectively, while the average annual percentage changes for incidence, prevalence, mortality, and disability-adjusted life years were 0.04, 0.50, 0.00%, and −0.02%, respectively. The projections from Bayesian age–period–cohort model showed that the burden of NRCAVD is expected to continue through 2050.ConclusionThe burden of NRCAVD in China has dramatically increased from 1990 to 2021, with a notable rise associated with aging. Male individuals appear to be more susceptible than female individuals and face higher mortality risks associated with NRCAVD in China. The forecast suggests that this trend will persist until 2050, highlighting NRCAVD as a significant public health challenge in China over the next three decades.